Peran Syahbandar Belawan dalam Melaksanakan Pengawasan Keselamatan Angkutan Laut - Liston Andy Saputra Butar – Butar; Taufik Siregar; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this research is to examine and analyze the legal rules regarding Syahbandar in Indonesian laws and regulations; the role played by Syahbandar Belawan and its obstacles in carrying out sea transportation safety. The method used is normative juridical research by analyzing laws and regulations and conceptual analysis by analyzing descriptive data. The results of the study show that the Syahbandar regulations are regulated in Law 17 of 2008 concerning shipping, Minister of Transportation Regulation No. 34 of 2012, Minister of Transportation Regulation No. 36 of 2012, and RI Government Regulation No. 9 of 2019. The future role of Syahbandar must be as the front guard in identifying cases of ship accidents at sea and must be able to change himself in a more professional direction and must routinely carry out ship inspections so that accidents during shipping can be minimized. The obstacles faced by Syahbandar in carrying out sea transportation safety supervision can be seen from a regulatory perspective, from an agency perspective, and from a facilities and infrastructure perspective. Suggestions that can be drawn from this thesis are that Belawan Syahbandar officers should provide educational supplies and train their employees to increase knowledge and skills that support supervisory activities, so that they can run properly so that the supervisory function of shipping safety can be improved.